2022
DOI: 10.1155/2022/4905583
|View full text |Cite
|
Sign up to set email alerts
|

Development of Authentic Assessment in Local Wisdom-Based Reading Learning

Abstract: This study aims to establish a reading learning evaluation model based on local wisdom. This type of research is development research that refers to the ADDIE (analyze, design, development, implementation, and evaluation) development model. The study subjects were conducted at two junior high schools with 65 students and 4 Indonesian teachers. The data collection techniques used in this study are tests, interviews, observations, and questionnaires. The results obtained through the preliminary research show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Amaliyah et al [49] state that literacy culture which involves local wisdom will be more efficient to enrich students' knowledge and improve their enthusiasm in learning reading. Another study is concluded that the use of local wisdom in increasing students' reading skill obtains good responses from material experts, linguists, and teachers [50].…”
Section: Introductionmentioning
confidence: 99%
“…Amaliyah et al [49] state that literacy culture which involves local wisdom will be more efficient to enrich students' knowledge and improve their enthusiasm in learning reading. Another study is concluded that the use of local wisdom in increasing students' reading skill obtains good responses from material experts, linguists, and teachers [50].…”
Section: Introductionmentioning
confidence: 99%
“…The use of nontest assessments is still limited, especially in the affective and psychomotor domains. However, in science, particularly in biology, assessment should cover all three domains simultaneously for the learning process to be meaningful [13,19,20]. Non-test assessments are used to assess learning outcomes using non-examination techniques aimed at obtaining assessment reports from the affective (attitude) and psychomotor (skills) domains [21].…”
Section: Introductionmentioning
confidence: 99%